4th symposium on primary breast cancer in older women. Theme: putting personalized care into practice (held: 3 March 2017) - Cheung, Kwok-Leung; Morgan, David; Brain, Etienne; Poortmans, Philip; Parks, Ruth; Korc-Grodzicki, Beatriz; Ugolini, Fiammetta; Shakir, Taner; Tsang, Janice; Stone, Heather; Kenis, Cindy; Perks, Graeme; et al. (Future Medicine, 2017)
Following the inception in 2010, the University of Nottingham hosted the 4th Symposium on Primary Breast Cancer in Older Women, under the auspices of the International Society of Geriatric Oncology, in March 2017, at East Midlands Conference Centre. This is the only meeting of its kind in the UK, now held biennially, aiming at a multidisciplinary audience, including patients, their carers and advocates. With a theme on ’Putting personalising care into practice’, this Symposium included sessions on ’local and systemic therapies’, ’new ideas’, ’patients and carers’, and ’challenging areas’, covered by an international and local faculty, interviewing patients and carers, and abstract presentations. Topics covered were practical and wide-ranging, including selecting for chemotherapy, radiotherapy and breast reconstruction, treating HER2-positive disease, and the roles of the geriatrician and geriatric oncology nurse.